Factors Influencing School Closure and Dismissal Decisions: Influenza A (H1N1), Michigan 2009. (January 2014) - Dooyema, Carrie A.; Copeland, Daphne; Sinclair, Julie R.; Shi, Jianrong; Wilkins, Melinda; Wells, Eden; Collins, Jim
ABSTRACT BACKGROUND In fall 2009, many US communities experienced school closures during the influenza A H1N1 pandemic (pH1N1) and the state of Michigan reported 567 closures. We conducted an investigation in Michigan to describe pH1N1‐related school policies, practices, and identify factors related to school closures. METHODS We distributed an online survey to all Michigan K‐12 school principals. Descriptive statistics and chi‐square tests summarize school policies, practices, adherence to government guidelines, and differences between schools that closed and those that remained open during the pandemic. RESULTS Of 4441 traditional K‐12 Michigan schools, 937 (21%) principals responded to our survey representing approximately 374, 000 students and 17, 700 teachers. The majority (88%) of schools had influenza preparedness plans and followed government school influenza guidelines. Among respondents, 15% (137/937) of schools closed in fall 2009 with high absenteeism as the primary reason for closure. Schools that closed reported significant illness in their school, had <300 students, and had invested substantial resources preparing and responding to influenza. CONCLUSIONS Adherence to government guidelines for schools appears high in Michigan. Closures occurred in schools that reported significant illness and were likely motivated by excessive absenteeism. Understanding factors related to closures during pH1N1 may inform future pandemic preparedness efforts.